2017
DOI: 10.1177/0333102417729113
|View full text |Cite
|
Sign up to set email alerts
|

Altered thalamic connectivity during spontaneous attacks of migraine without aura: A resting-state fMRI study

Abstract: Background Functional connectivity of brain networks may be altered in migraine without aura patients. Functional magnetic resonance imaging (fMRI) studies have demonstrated changed activity in the thalamus, pons and cerebellum in migraineurs. Here, we investigated the thalamic, pontine and cerebellar network connectivity during spontaneous migraine attacks. Methods Seventeen patients with episodic migraine without aura underwent resting-state fMRI scan during and outside of a spontaneous migraine attack. Prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 41 publications
(41 reference statements)
2
88
0
1
Order By: Relevance
“…21,22 The thalamus seemed to be only significantly altered in patients with MTH in this study, though recently published reports have identified the significance of this brain region as a functional pain-signaling relay. 23,24 Additionally, the thalamus volume has been found to be altered in patients with medication overuse headache and MTH with and without aura. [23][24][25] The amygdala has also been demonstrated to have volumetric decreases in patients with chronic MTH, demonstrating an inverse relationship to the frequency of migraine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 The thalamus seemed to be only significantly altered in patients with MTH in this study, though recently published reports have identified the significance of this brain region as a functional pain-signaling relay. 23,24 Additionally, the thalamus volume has been found to be altered in patients with medication overuse headache and MTH with and without aura. [23][24][25] The amygdala has also been demonstrated to have volumetric decreases in patients with chronic MTH, demonstrating an inverse relationship to the frequency of migraine.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Additionally, the thalamus volume has been found to be altered in patients with medication overuse headache and MTH with and without aura. [23][24][25] The amygdala has also been demonstrated to have volumetric decreases in patients with chronic MTH, demonstrating an inverse relationship to the frequency of migraine. 26 These structures are more prominently implicated in the limbic circuitry, which is presumed to be more related to pain perception than pain sensation.…”
Section: Discussionmentioning
confidence: 99%
“…The thalamus has been described as being most likely to be involved in dysfunctional pain modulation and processing in migraine . In addition, during migraine attacks, the network connectivity of the right thalamus with pain‐modulating and pain‐encoding cortical areas is affected . In 1 study in rats, intravenous or microiontophoretically naratriptan potently and reversibly modulated trigemino‐vascular thalamic neuronal firing triggered by electrical stimulation of the superior sagittal sinus .…”
Section: Discussionmentioning
confidence: 97%
“…100 In addition, during migraine attacks, the network connectivity of the right thalamus with pain-modulating and painencoding cortical areas is affected. 101 In 1 study in rats, intravenous or microiontophoretically naratriptan potently and reversibly modulated trigemino-vascular thalamic neuronal firing triggered by electrical stimulation of the superior sagittal sinus. 102 The peak inhibition was observed between 5 and 10 minutes after intravenous administration; 102 however, the blood-brain barrier was…”
Section: Summary Of Several Likely Sites Of Actions Of Triptans Thamentioning
confidence: 99%
“…Çalışmalar, ağrı-nosiseptif ve görsel uyaranlara aşırı duyarlılık gibi tipik migren semptomlarının, anormal aktivasyon ve trigeminovasküler ve talamik yolların duyarlılığı sonucunda ortaya çıktığını göstermiştir (20). Talamustaki değişiklikler migrenli hastalarda daha önceki çalışmalarda gösterilmiştir (5,(21)(22)(23). Bizim çalışmamızda seyrek ağrı sıklığı olan grupta talamus volümü artmış olarak bulundu.…”
Section: Discussionunclassified